Realizacja Zintegrowanego Programu Rozwoju Regionalnego w województwie pomorskim (2004-2006) - Kempa, Jarosław; Paczoski, Andrzej (Performance of the Integrated Regional Operational Programme in Pomorskie Voivodeship (2004-2006), 2008)
The paper is an attempt to evaluate the first Operational Programme in the programming period 2004-2006, after Poland's accession to the EU. The aim of the programme was to support identified regional strategy. The paper describes the programme itself and also lists issues and problematic areas in the region. The involvement of the programmes' beneficiaries has been analyzed and presented by geographic area, the programme's priorities, and measures. IROP played an important role in integrating local and regional communities around joint projects and objectives and had a clear educational value in providing information to many regional actors who intend to apply for funds under Regional Operation Programme for the period 2007-2013. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 205-216